Patos w retoryce filmowej. Na podstawie "Yodok stories" Andrzeja Fidyka - Fiołek-Lubczyńska, Bogumiła (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The article relates to the use of rhetoric in documentary film. Pathos is one of many ways of creating a persuasive documentary. According to Andrzej Fidyk, modern documentary film must be attractive to the viewer, otherwise, nobody will watch it. Hence the director decided to use persuasive elements in his film. Pathos is a tool for arousing strong feelings in the viewer. The source of those feelings is the presentation of power and concentration camps in the form of a musical extravaganza.